2021
DOI: 10.53023/p.rasayan-20211221
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and biological activities of naturally occurring apocarotenoid bixin

Abstract: The naturally occurring apo-carotenoid bixin is obtained from annatto (Bixa orellana). It is unique among the natural carotenoids through its water solubility and easily extractability from the seed coat of Bixa orellana. Bixin is (2E,4E,6E,8E,10E,12E,14E,16Z, 18E)-20- methoxy-4,8,13,17-tetramethyl-20-oxicosa 2,4,6,8,10,12,14,16,18-nonaenoic acid, an apo-carotenoid which is a terpenoid compound derived from the oxidative cleavage of carotenoids. Several biological activities of bixin has been reported earlier … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…Synthesis of KLAuNPs: Synthesis of RLAuNPs was carried out following the procedure as described previously. 11 A stock methanolic extract of leaf of Kakoli was prepared (6900 µg/mL). The stock solution of the extract was diluted in vials of capacity 4 mL (Figure 3A) to prepare a series of the solutions in water.…”
Section: Synthesis Of Klagnpsmentioning
confidence: 99%
See 3 more Smart Citations
“…Synthesis of KLAuNPs: Synthesis of RLAuNPs was carried out following the procedure as described previously. 11 A stock methanolic extract of leaf of Kakoli was prepared (6900 µg/mL). The stock solution of the extract was diluted in vials of capacity 4 mL (Figure 3A) to prepare a series of the solutions in water.…”
Section: Synthesis Of Klagnpsmentioning
confidence: 99%
“…Synthesis of KLAgNPs in water medium was carried out in an identical method of KLAuNPs preparation keeping the concentrations of the leaf extract identical. 11 Aliquots of AgNO3 solution (100 µL, 14.0 mM) in water were added to each of the vials of capacity of 4 mL. The final volume of the mixtures was 2 mL each and the final concentration of AgNO3 in the mixtures was 0.7 µg/mL in each vial (Figure 4).…”
Section: Synthesis Of Klagnpsmentioning
confidence: 99%
See 2 more Smart Citations
“…5,6 Previous reports from our laboratory have shown that the pseudobulb of Crepidium acuminatum (Jeevak), 7 extract of Roscoea purpurea Sm. (Kakoli), 8,9 Rhizome Extract of Polygonatum cirrhifolium (Mahameda) 10 and, extracts of Habenaria Edgeworthii (Vrddhi) 11 and Habenaria intermedia (Rddhi) 12,13 are reach in antioxidants. Hence, it occurred to us that the leaf extract of Vrddhi may also be rich in antioxidants.…”
mentioning
confidence: 99%